2007
DOI: 10.1007/s10558-007-9045-5
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Assessment of Cerebral Autoregulation from Spontaneous Blood Pressure and Cerebral Blood Flow Fluctuations

Abstract: Cerebral autoregulation (CA) is an most important mechanism responsible for the relatively constant blood flow supply to brain when cerebral perfusion pressure varies. Its assessment in nonacute cases has been relied on the quantification of the relationship between noninvasive beat-to-beat blood pressure (BP) and blood flow velocity (BFV). To overcome the nonstationary nature of physiological signals such as BP and BFV, a computational method called multimodal pressure-flow (MMPF) analysis was recently develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 35 publications
2
90
0
1
Order By: Relevance
“…However, it is still impossible to recognize which IMFs are dominant factors for these diseases or events accurately. Although the obvious physiological response of patients within the particular frequency band through Valsalva maneuver test [28] is helpful to trace the IMF that is more related to this event, it is still intended to test for this kind of experiment. Most bio-signal analysis situations do not have this kind of patient stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still impossible to recognize which IMFs are dominant factors for these diseases or events accurately. Although the obvious physiological response of patients within the particular frequency band through Valsalva maneuver test [28] is helpful to trace the IMF that is more related to this event, it is still intended to test for this kind of experiment. Most bio-signal analysis situations do not have this kind of patient stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested that ABP-FV phase lag could serve as an index of cerebral autoregulation. The same method can be used for continuous monitoring of cerebral autoregulation, analyzing spontaneous fluctuation of ABP [18].…”
Section: Multimodal Decompositionmentioning
confidence: 99%
“…Inclusion criteria were met by 14 controlled studies and 13 observational studies. Three studies were excluded because of unclear timing of measurements after stroke onset, [21][22][23] and 1 was excluded because TIA and minor stroke patients were grouped together. 24 Hence, 23 publications were eligible for review.…”
Section: Literaturementioning
confidence: 99%